EWS‐FLI1 impairs aryl hydrocarbon receptor activation by blocking tryptophan breakdown via the kynurenine pathway. Issue 14 (21st June 2016) - Mutz, Cornelia N.; Schwentner, Raphaela; Kauer, Maximilian O.; Katschnig, Anna M.; Kromp, Florian; Aryee, Dave N. T.; Erhardt, Sophie; Goiny, Michel; Alonso, Javier; Fuchs, Dietmar; Kovar, Heinrich
Abstract : Ewing sarcoma (ES) is an aggressive pediatric tumor driven by the fusion protein EWS‐FLI1. We report that EWS‐FLI1 suppresses TDO2‐mediated tryptophan (TRP) breakdown in ES cells. Gene expression and metabolite analyses reveal an EWS‐FLI1‐dependent regulation of TRP metabolism. TRP consumption increased in the absence of EWS‐FLI1, resulting in kynurenine and kynurenic acid accumulation, both aryl hydrocarbon receptor (AHR) ligands. Activated AHR binds to the promoter region of target genes. We demonstrate that EWS‐FLI1 knockdown results in AHR nuclear translocation and activation. Our data suggest that EWS‐FLI1 suppresses autocrine AHR signaling by inhibiting TDO2‐catalyzed TRP breakdown. Abstract :